Successful pregnancy soon after oral contraceptive-associated malignant hypertension. Issue 661 (November 1980) - Silas, J. H.; Singer, A.; Woods, H. F.; Brown, V. A.
Abstract : A woman who developed malignant hypertension while taking a very low oestrogen oral contraceptive underwent an uncomplicated pregnancy conceived 3 months later. Her BP was well controlled with propranolol alone.